Ablation of the cardiac ryanodine receptor phospho-site Ser2808 does not alter the adrenergic response or the progression to heart failure in mice. Elimination of the genetic background as critical variable. (February 2017) - Alvarado, Francisco J.; Chen, Xi; Valdivia, Héctor H.
Abstract: Background: Phosphorylation of the cardiac ryanodine receptor (RyR2) phospho-site S2808 has been touted by the Marks group as a hallmark of heart failure (HF) and a critical mediator of the physiological fight-or-flight response of the heart. In support of this hypothesis, mice unable to undergo phosphorylation at RyR2-S2808 (S2808A) were significantly protected against HF and displayed a blunted response to adrenergic stimulation. However, the issue remains highly controversial because several groups have been unable to reproduce these findings. An important variable not considered before is the genetic background of the mice used to obtain these divergent results. Methods and results: We backcrossed a RyR2-S2808A mouse into a congenic C57Bl/6 strain, the same strain used by the Marks group to conduct their experiments. We then performed several key experiments to confirm or discard the genetic background of the mouse as a relevant variable, including induction of HF by myocardial infarction and tests of integrity of adrenergic response. Congenic C57Bl/6 harboring the S2808A mutation showed similar echocardiographic parameters that indicated identical progression towards HF compared to wild type controls, and had a normal response to adrenergic stimulation in whole animal and cellular experiments. Conclusions: The genetic background of the different mouse models is unlikely to be the source of the divergent results obtained by the Marks group in comparison to several other groups. Cardiac adrenergic response and progression towards HF proceed unaltered in mice harboring the RyR2-S2808A mutation. Preventing RyR2-S2808 phosphorylation does not preclude a normal sympathetic response nor mitigates the pathophysiological consequences of MI.